The genesis of Carlow Castle: A unique Australian orogenic Cu-Co-Au deposit in the Archean Pilbara Craton. Issue 1 (1st December 2019) - Fox, David; Spinks, Sam; Pearce, Mark; Vaillant, Margaux Le; Thorne, Robert; Barham, Milo; Aspandiar, Mehrooz
Summary: Carlow Castle is a Cu-Co-Au deposit situated within the western Pilbara Craton of Western Australia. Whilst Carlow Castle is the oldest discovered copper deposit in the Pilbara region, having been initially discovered in 1882, no detailed study of the ore mineralisation has ever been undertaken. After being long abandoned, a recent drilling campaign through 2018 uncovered an economically significant and geologically complex system of Cu-Co-Au mineralisation with a current resource estimate for Carlow Castle of 7.7Mt @ 1.06g/t Au, 0.51% Cu, and 0.08% Co, making it one of Australia's most significant Cu-Co-Au deposits. This mineralisation was analysed using a variety of geochemical and mineralogical techniques in order to provide the first constraint on its genesis. This analysis suggests that Carlow Castle is a hydrothermal Cu-Co-Au deposit, with mineralisation hosted in sulphide-rich quartz veins throughout a pervasively chloritised shear zone in an Archaean mafic volcano-sedimentary sequence. Within these ore veins, the sulphide mineralogy is dominated by pyrite (FeS2), chalcopyrite (CuFeS2), chalcocite (Cu2S), and cobaltite (CoAsS). Here we present the findings of the first detailed study on the nature of the Cu-Co-Au mineralisation at Carlow Castle and propose an orogenic model for the genesis of this unique deposit. It is proposed that the orogenic event that gave rise to Carlow Castle is related to the initial assembly of the Pilbara Craton during the Archean.